6(9-b)=-1

Simple and best practice solution for 6(9-b)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(9-b)=-1 equation:


Simplifying
6(9 + -1b) = -1
(9 * 6 + -1b * 6) = -1
(54 + -6b) = -1

Solving
54 + -6b = -1

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-54' to each side of the equation.
54 + -54 + -6b = -1 + -54

Combine like terms: 54 + -54 = 0
0 + -6b = -1 + -54
-6b = -1 + -54

Combine like terms: -1 + -54 = -55
-6b = -55

Divide each side by '-6'.
b = 9.166666667

Simplifying
b = 9.166666667

See similar equations:

| lnx=3.19 | | 5+ln(x+2)=4 | | ln(x)=3.19 | | -0.2(34.3+3x)=0.1x | | 7c-(-8)-2c=17 | | (5x-1)2=22 | | -5x-4.2=121 | | 15.3=67-y | | a-x=0.1 | | -5x-x=-3 | | -5x+4.2=121 | | 5(x+2)=1+5x | | -5x-4=121 | | 9+6x=-1 | | 0.02p+0.07(1500-9)=70 | | 32-5m=5 | | 2(5+3n)= | | 2(5+3n)= | | N^4+6*n^3=0 | | 5x+12=4-(3x) | | 5x+12=4-3x | | 7m+6m+5=0 | | 1x-y= | | p^2+5p+2p=0 | | x-1=7x-4 | | x-6=x-12 | | x^2+x+100=0 | | 3ax-8y+13=0 | | 60-3y=6y+16 | | 170-9x=10x+20 | | 10-9y=30-23y | | -124-8y=10y+20 |

Equations solver categories